Techniques of Treasury Debt Management - Gaines, Tilford C. (New York : Joint publication of the Graduate School of Business, Columbia University, and Free Press of Glencoe, 1962)
The book is divided into two parts: a detailed historical survey of debt management in the United States from the Civil war through 1957; the second part deals with current problems of debt management and sets forth suggested policies for dealing with them.
Includes bibliographical references (p. 301-308) and index.
osc 20/06/17
Loans
Keywords: Debts, Public